2021
DOI: 10.1111/1744-9987.13587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise therapy on the persistence of physical function, exercise habits, and self‐efficacy after cessation of exercise in patients undergoing hemodialysis: A nonrandomized control trial

Abstract: The present study investigated the sustained effect of exercise therapy discontinuation in patients under hemodialysis with low physical function. Seven subjects in the exercise group and eight in the control group who had low physical function (short physical performance battery; SPPB ≤ 9 points) were included in the study. The exercise group received 6 months of intradialytic exercise, followed by 6 months of observation. We assessed SPPB, grip strength, self‐efficacy (SE), and exercise habits in both the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…A previous study found that the older the person, the longer the run completion time [ 16 ], which was consistent with our findings. In addition, our study included exercise habits as a variable and found that compared to those who did not have an exercise habit, participants who regularly exercised 4 to 6 times a week required substantially less time to complete the 1600-meter run, which was consistent with the result of another study [ 53 ].…”
Section: Discussionsupporting
confidence: 86%
“…A previous study found that the older the person, the longer the run completion time [ 16 ], which was consistent with our findings. In addition, our study included exercise habits as a variable and found that compared to those who did not have an exercise habit, participants who regularly exercised 4 to 6 times a week required substantially less time to complete the 1600-meter run, which was consistent with the result of another study [ 53 ].…”
Section: Discussionsupporting
confidence: 86%
“…Exercise, providing positive responses and adaptations, might affect the circulatory levels of two neurotransmitters (serotonin and dopamine), upregulate the BDNF-Serotonin systems [ 38 ], and decrease anxiety and depression. Additionally, there were several plausible explanations of the beneficial effects of physical exercise include reductions in inflammatory and oxidant markers [ 14 , 39 ], which are activated during mental disorders, improvement of self-efficacy [ 40 ], as well as enhanced hope, the second finding in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of older patients undergoing hemodialysis showed a significant effect of exercise on LES [33,34], whereas others did not [35,36]. Exercise tolerance was also significantly affected in some studies [33,37], but not in others [35], Yamaguchi et al [38] showed, in a non-RCT, that a 6-month intradialytic exercise program for patients (mean age, 69.1 ± 7.6 years) with low physical function (SPPB score <9 points) significantly improved their SPPB scores. Chen et al [34] showed the effect of exercise on the SPPB score but not on the 10-m walking speed in an RCT of a 4-month intradialytic resistance exercise program for advanced-age patients (mean age, 71.1 ± 12.6 years).…”
Section: Plos Onementioning
confidence: 95%